Memajukan Kehidupan Budaya Yang Islami Melalui Naskah Sunda Kuno Para Ulama Terdahulu - Sukmawaty, Fenty; Anandari, Afni Malika; Maharani, Siti Rinita (Jurnal ETAM, 2025)
The culture that is rooted in the midst of society today is a legacy from the ancestors. One way for the ancestors to preserve the culture is to express their ideas or culture in writing. Ancient Sundanese manuscripts are cultural products of the past, the work of previous scholars who stored intellectual and spiritual wealth full of local wisdom values. Through the analysis of ancient Sundanese manuscripts scattered, both domestically and abroad, it was found that the manuscripts covered various aspects of community life in the past such as politics, economics, socio-culture, and history. The purpose of this service is to introduce ancient Sundanese manuscripts as a cultural heritage of the previous scholars to the women of the Taklim Branch of Aisyiyah Gegerbitung Branch, Sukabumi Regency so that the work of the previous scholars can be a source of inspiration in building a nation based on Islamic values and local wisdom today. The results of this service activity show that people often encounter various types of ancient Sundanese manuscripts in their daily lives, but do not realize how important these manuscripts are. Therefore, this service is a very important activity for the preservation and utilization of ancient Sundanese Manuscripts as an effort to enrich and advance Islamic cultural life in Indonesia.